Preventing and Therapeutic Effect of Propolis in Radiotherapy Induced Mucositis of Head and Neck Cancers: A Triple-Blind, Randomized, Placebo-Controlled Trial - Javadzadeh Bolouri, Abbas (Iran J Cancer Prev, 2015)
BACKGROUND: Mucositis is one of the acute complications of radiotherapy which can ulcerate oral mucosa and cause severe pain and discomfort which can affect oral normal function. Propolis is a natural source of flavenoid which has antiulcer, antibacterial, antifungal, healing and anti-inflammatory effects. Using such an affordable compound without any bad smell or taste that has reasonable price can help the radiotherapy undergoing patients. OBJECTIVES: Our goal is assessing the preventing and therapeutic effect of propolis in radiotherapy induced mucositis in patients with head and neck cancer. PATIENTS AND METHODS: In a randomized triple blind clinical trial, 20 patient were selected randomly to swish and swallow 15 ml of water based extract of propolis mouth wash 3 times a day in the case group (n = 10) and 15 ml placebo mouth wash in control group (n = 10). we use NIC-CTC scale for determining mucositis grading. RESULTS: We use T-test, Man-Whitney, Chi-square, and Friedman as analyzing tests. Case group had significantly (P < 0.05) lower grade of mucositis in all of the follow-ups, but xerostomia is not significantly different in two groups (P > 0.05). CONCLUSIONS: This is a pilot study which shows water based extract of propolis efficiently prevents and heals radiotherapy induced mucositis.